A study of saliva lubrication using a compliant oral mimic. (July 2019) - Carpenter, G.; Bozorgi, S.; Vladescu, S.; Forte, A.E.; Myant, C.; Potineni, R.V.; Reddyhoff, T.; Baier, S.K.
Abstract: Due to ethical issues and the difficulty in obtaining biological tissues, it is important to find synthetic elastomers that can be used as replacement test media for research purposes. An important example of this is friction testing to understand the mechanisms behind mouthfeel attributes during food consumption ( e.g. syrupy, body and clean finish), which requires an oral mimic. In order to assess the suitability of possible materials to mimic oral surfaces, a sliding contact is produced by loading and sliding a hemispherical silica pin against either a polydimethyl siloxane (PDMS), agarose, or porcine tongue sample. Friction is measured and elastohydrodynamic film thickness is calculated based on the elastic modulus of the samples, which is measured using an indentation method. Tests were performed with both saliva and pure water as the lubricating fluid and results compared to unlubricated conditions. PDMS mimics the tongue well in terms of protein adhesion, with both samples showing significant reductions in friction when lubricated with saliva versus water, whereas agarose showed no difference between saliva and water lubricated conditions. This is attributed to PDMS's OSi(CH3)2- group which provides excellent adhesion for the saliva protein molecules, in contrast with the hydrated agarose surface. The measured modulus of the PDMS (2.2 MPa) is however significantly greater than that of tongue (3.5 kPa) and agarose (66–174 kPa). This affects both the surface (boundary) friction, at low sliding speeds, and the entrained elastohydrodynamic film thickness, at high speeds. Utilising the transparent PDMS sample, we also use fluorescence microscopy to monitor the build-up and flow of dyed-tagged saliva proteins within the contact during sliding. Results confirm the lubricous boundary film forming nature of saliva proteins by showing a strong correlation between friction and average protein intensity signals (cross correlation coefficient = 0.87). This demonstrates a powerful method to study mouthfeel mechanisms. Graphical abstract: Image 1 Highlights: Tongue surfaces are characterised in terms of stiffness and lubrication mechanisms. The suitability of synthetic materials, which can replicate biological samples in simulated mouthfeel tests, are assessed. Protein adhesion and stiffness are shown to be key properties for synthetic materials to mimic oral surfaces effectively. Fluorescence microscopy is demonstrated as a tool to analyse mouthfeel.